2019
DOI: 10.1088/1757-899x/546/7/072007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ni Catalyst Supported on SiO2-ZrO2 Binary Oxide for Hydrodeoxygenation of Phenol

Abstract: Hydrodeoxygenation is a one-step reaction that involve the hydrogenation of unsaturated carbon followed with the deoxygenation of the carbon-oxygen bond. This reaction is effective for converting biomass-derived chemicals from bio-oils, fats, woods, and lignocellulosic materials into biofuels using metal-based oxide catalysts. A Ni based-metal oxide catalyst is reported for hydrodeoxygenation reaction of phenol. The catalyst was prepared by a wet-impregnation method using Ni(NO3)2.6H2O dissolved in deionized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The binary oxide Al2O3-ZrO2 and SiO2-ZrO2 was previously prepared in a 1:1 (wt/wt) ratio according to the reported methods [19,20]. 10 g of Al2O3-ZrO2 was prepared by dissolving 13 g of ZrOCl2.8H2O in deionized water (DI) with the dropwise addition of NH4OH until pH 8 was identified by the formation of Zr(OH)4 as a white precipitate.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The binary oxide Al2O3-ZrO2 and SiO2-ZrO2 was previously prepared in a 1:1 (wt/wt) ratio according to the reported methods [19,20]. 10 g of Al2O3-ZrO2 was prepared by dissolving 13 g of ZrOCl2.8H2O in deionized water (DI) with the dropwise addition of NH4OH until pH 8 was identified by the formation of Zr(OH)4 as a white precipitate.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…A reverse-phase formation from amorphous to crystalline SiO2 was detected after Ni impregnation. To understand the effect of binary support on Ni catalyst, we tested Ni/SiO2-ZrO2 for phenol hydrodeoxygenation in a stainless autoclave batch reactor [20]. The catalyst showed remarkable activity for ring hydrogenation with the selective formation of cyclohexanol and cyclohexanone.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, because of the high optical transparency, superhydrophobic and cytotoxic properties of SiO2 (silica), they have been used in different application fields such as optoelectronic devices, self-cleaning materials and drug delivery systems [7]. Although SiO2 used as a support material in the catalysis studies, there is no work has been observed in SiO2 supported NiO in the magnetization studies according to our knowledge until now in the literatüre [8]. However, Husain and co-workers explained that SiO2 coated Fe3O4 exhibited enhancing magnetism due to non-toxic properties of SiO2 [9].…”
Section: Introductionmentioning
confidence: 99%